LITERATUR REVIEW: PENERAPAN PIJAT KAKI DAN RENDAM AIR HANGAT CAMPURAN KENCUR TERHADAP EDEMA KAKI IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS I WANGON, BANYUMAS - Tri Endah Widi Lestari; Melyana Nurul Widyawati; Admini Admini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
Foot edema or swelling in the legs is found most in pregnant women in the third trimester, prioritizing the principles of care for mothers and babies to descrease discomfort, the need for prevention and appropriate care for pregnant women. The purpose of this article is to review some of the literature related to the application of foot massage and soak in warm kaempferia galanga L mixed water to reduce edema of pregnant women in the third trimester.This article method is a form of analysis metadata research using literature review. The source used in the electronic database is EBSCO, and google scholar with the keywords foot massage, edema of the pregnant mother's feet/foot edema late pregnancy, soaking warm water, kaempferia galanga L as antiinflammatory. The article used is between 2009-2018, found 1 international journal and 14 national journals with 6main journals and 9 study supporting journals.The results of foot massage and warm water soaked with kaempferia galanga L have not been applied in a similar manner, but from each treatment combined so as to reduce physiological edema of pregnant women in the third trimester. The discussion of the literature review of six journal articles can be combined and examined that intervening in foot edema in pregnant women naturally by using foot massage and soaking warm water mixed with Kaempferia Galanga L in a safe and effective intervention category to reduce edema of pregnant women.The conclusion of this article was the application of foot massage therapy and warm water soaking the mixture of Kaempferia Galanga L effective in reducing physiological foot edema in third trimester pregnant women who have not received any treatment.